2020
DOI: 10.33448/rsd-v9i7.4729
|View full text |Cite
|
Sign up to set email alerts
|

Simulação do processo de produção de uma indústria de água mineral pelo método system dynamics

Abstract: This research was conducted with the objective of implementing a computer model to simulate the steps that comprise the operational flowchart of a mineral water industry, using the software Stella 8.0. The model defined as dynamic, stochastic and discrete consisted of eleven interconnected blocks. It was built following the steps of characterizing the real system, creating the conceptual model, structuring and verification of computational model, data collection, and model validation. From data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Scatterplots, for example, provide some information about the presence of outliers, the relationship between variables (correlations), and the behavior of the data over time (Vonesh, 2014;Sher et al, 2017). Silva et al (2020) demonstrated the importance and ease of use of computational tools to analyze the data, adjust the distributions and verify the model. Making it a useful tool in reducing errors, costs, and processing time.…”
Section: Introductionmentioning
confidence: 99%
“…Scatterplots, for example, provide some information about the presence of outliers, the relationship between variables (correlations), and the behavior of the data over time (Vonesh, 2014;Sher et al, 2017). Silva et al (2020) demonstrated the importance and ease of use of computational tools to analyze the data, adjust the distributions and verify the model. Making it a useful tool in reducing errors, costs, and processing time.…”
Section: Introductionmentioning
confidence: 99%